2019
DOI: 10.1038/s42004-019-0233-1
|View full text |Cite
|
Sign up to set email alerts
|

P band intermediate state (PBIS) tailors photoluminescence emission at confined nanoscale interface

Abstract: The availability of a range of excited states has endowed low dimensional quantum nanostructures with interesting luminescence properties. However, the origin of photoluminescence emission is still not fully understood, which has limited its practical application. Here we judiciously manipulate the delicate surface ligand interactions at the nanoscale interface of a single metal nanocluster, the superlattice, and mesoporous materials. The resulting interplay of various noncovalent interactions leads to a preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(96 citation statements)
references
References 69 publications
(104 reference statements)
2
94
0
Order By: Relevance
“…Obviously, the change of optical properties is caused by the structural discrepancy of two intermediate states, suggesting the varied overlapping of the two p orbitals of O atoms from hydroxide groups and /or 4-NP (49). This finally determines the reaction kinetic of 4-NP reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the change of optical properties is caused by the structural discrepancy of two intermediate states, suggesting the varied overlapping of the two p orbitals of O atoms from hydroxide groups and /or 4-NP (49). This finally determines the reaction kinetic of 4-NP reduction.…”
Section: Resultsmentioning
confidence: 99%
“…This interpretation gives a completely new insight into the luminescent principle of MNCs, but we cannot completely preclude the role of the metal core for the PL emission. Very most recently, based on the complimentary characterizations of steady-state absorption, excitation, and time-resolved PL spectroscopy, we definitively identify that the induced p band intermediate state (PBIS) stems from the overlapping of p orbitals of the paired or more adjacent heteroatoms (O and S) from the surface-protected ligands on the metal NCs, which can be Very most recently, based on the complimentary characterizations of steady-state absorption, excitation, and time-resolved PL spectroscopy, we definitively identify that the induced p band intermediate state (PBIS) stems from the overlapping of p orbitals of the paired or more adjacent heteroatoms (O and S) from the surface-protected ligands on the metal NCs, which can be Very most recently, based on the complimentary characterizations of steady-state absorption, excitation, and time-resolved PL spectroscopy, we definitively identify that the induced p band intermediate state (PBIS) stems from the overlapping of p orbitals of the paired or more adjacent heteroatoms (O and S) from the surface-protected ligands on the metal NCs, which can be considered as a dark state at the metal-NCs interface to activate the triplet site of the surface chromophores by enhancing intersystem crossing [43]. Figure 15 showed that the water-soluble and oil-soluble MNCs with identical size synthesized by a ligand-exchange strategy (denoted as Au NCs@GSH and Au NCs@DT, respectively) exhibited the strong solvent-enhanced PL emission behavior, and that it is very interesting that the number and intensity of PL emission was strongly dependent on the type of used surface-protective ligands, even though the metal core remains intact.…”
Section: Our P Band Intermediate State (Pbis) Model Dominates the Phomentioning
confidence: 89%
“…We definitively confirmed that the pairing of surface ligands could serve as an exact chromophore for PL emission, which has nothing to do with the metal core. considered as a dark state at the metal-NCs interface to activate the triplet site of the surface chromophores by enhancing intersystem crossing [43]. Figure 15 showed that the water-soluble and oil-soluble MNCs with identical size synthesized by a ligand-exchange strategy (denoted as Au NCs@GSH and Au NCs@DT, respectively) exhibited the strong solvent-enhanced PL emission behavior, and that it is very interesting that the number and intensity of PL emission was strongly dependent on the type of used surface-protective ligands, even though the metal core remains intact.…”
Section: Our P Band Intermediate State (Pbis) Model Dominates the Phomentioning
confidence: 99%
See 2 more Smart Citations